2019
DOI: 10.1155/2019/7136763
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus and Associated Factors among Health Professionals in University of Gondar Hospital, Northwest Ethiopia

Abstract: Introduction. Hepatitis B virus infection is one of the commonest occupational risks in healthcare workers. However; there is limited evidence regarding the prevalence of hepatitis in health professionals in Ethiopia. Objective. This study was aimed at assessing the prevalence of hepatitis B and associated factors in health professionals. Methods. Institution based cross-sectional study was conducted among health professionals at University of Gondar Hospital from January to February, 2015. Self-administered q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…All the included studies were cross-sectional study designs and the most recent was conducted in 2019. Regarding regional coverage of HBV prevalence studies, more than half of the studies were obtained from Amhara region 22 (36.7%) [20, 29, 31, 3638, 44, 46, 49, 50, 53, 58, 62, 63, 6769, 71, 75, 78, 79, 82], Oromia region 12(20%) [32, 34, 41, 47, 48, 56, 60, 61, 64, 83, 85, 87], and Southern Nations, Nationalities and Peoples Region (SNNPR) 9(15%) [30, 43, 52, 65, 66, 70, 74, 76, 86]. The sample size across the studies was ranged from 108 [53] to 35,435 [44] obtained from the Amhara region.…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies were cross-sectional study designs and the most recent was conducted in 2019. Regarding regional coverage of HBV prevalence studies, more than half of the studies were obtained from Amhara region 22 (36.7%) [20, 29, 31, 3638, 44, 46, 49, 50, 53, 58, 62, 63, 6769, 71, 75, 78, 79, 82], Oromia region 12(20%) [32, 34, 41, 47, 48, 56, 60, 61, 64, 83, 85, 87], and Southern Nations, Nationalities and Peoples Region (SNNPR) 9(15%) [30, 43, 52, 65, 66, 70, 74, 76, 86]. The sample size across the studies was ranged from 108 [53] to 35,435 [44] obtained from the Amhara region.…”
Section: Resultsmentioning
confidence: 99%
“…Forbye, the 12-month BBFs prevalence in the primary studies ranged from 16.5 [12] to 67.5% [23]. In parallel, the lifetime prevalence ranged from 28.8 [14] and 81.0% [33]. This 12-month pooled prevalence estimate was almost comparable from the pooled estimate from East Africa (47.3%) [9], Côte d'Ivoire, Mali, and Senegal (45.7%) [51], and a study by Bi P et al from Australia, revealed that 42% of HCWs had body fluid exposures in a year on their study [52].…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of 12 months BBFs among the Ethiopian HCWs ranged from 16.5 [12] to 67.5% [23] in Addis Ababa Region. The lifetime prevalence of BBFs varied from 28.8% in the Harari Region [14] to 81.0% in the Amhara Region [33]. In this review, a low risk of bias was realized in 32 (88.9%) of the included studies (Additional file 3).…”
Section: Characteristics Of the Appended Studiesmentioning
confidence: 93%
“…All these health workforces are included in this study because these peoples have a relatively high occupational exposure to the HepB virus compared to the general population and in one way or another way they are involved in the Ethiopian healthcare service delivery. In Ethiopia, the risk of exposure is high among physicians, clinical nurses, midwives, laboratory technicians, and anesthetists consecutively 12 . Accordingly, this study would be implemented across all health facilities i.e.…”
Section: Methodsmentioning
confidence: 99%